2001
DOI: 10.1093/jexbot/52.357.839
|View full text |Cite
|
Sign up to set email alerts
|

Influx and accumulation of Cs+ by the akt1 mutant of Arabidopsis thaliana (L.) Heynh. lacking a dominant K+ transport system

Abstract: An extensive literature reports that Cs(+), an environmental contaminant, enters plant cells through K(+) transport systems. Several recently identified plant K(+) transport systems are permeable to Cs(+). Permeation models indicate that most Cs(+) uptake into plant roots under typical soil ionic conditions will be mediated by voltage-insensitive cation (VIC) channels in the plasma membrane and not by the inward rectifying K(+) (KIR) channels implicated in plant K nutrition. Cation fluxes through KIR channels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 1 publication
4
46
0
Order By: Relevance
“…For example, it has been suggested that l37 Cs uptake into plants is primarily through Voltage Independent Cation channels in root membranes [6]. Our research has supported this suggestion by demonstrating the irrelevance of other potential transporter proteins to 137 Cs uptake [7]. The results reported here suggest that high l37 Cs uptake in the CaryophyHales might arise from VIC channel characteristics.…”
Section: Discussionsupporting
confidence: 80%
“…For example, it has been suggested that l37 Cs uptake into plants is primarily through Voltage Independent Cation channels in root membranes [6]. Our research has supported this suggestion by demonstrating the irrelevance of other potential transporter proteins to 137 Cs uptake [7]. The results reported here suggest that high l37 Cs uptake in the CaryophyHales might arise from VIC channel characteristics.…”
Section: Discussionsupporting
confidence: 80%
“…Barkley (Mori et al 2012). The molecular mechanism of Cs absorption into cells in the top tissues may be similar to the root absorption mechanism, which occurs through K transporters (White and Broadley 2000;Broadley et al 2001;Britto and Kronzucker 2008;Kanter et al 2010;Kobayashi et al 2010). After the disaster, during the rainy season in Japan, some of the soluble components of the fallout may have moved downward on the surface of bamboo shoots into the litter on the soil surface (Nuclear Regulation Authority n.d.b) or into the surface soils below the litter layer, or could have been absorbed by the condensed aerial roots around the nodes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is also current research into Cs uptake mechanisms in plants, often with a view to genetically manipulating Cs uptake. When the genes associated with uptake mechanisms for Cs have been identified (11), or when utilising Quantitative Trail Loci that have already been described in Arabidopsis (12), the biodiversity 'landscape' described through phylogeny could provide a useful conduit to application in the field. This might be for safe crops or for those with enhanced uptake of radioceasium.…”
Section: Discussionmentioning
confidence: 99%